Influence of Workplace Environment and Ergonomic Posture on Musculoskeletal Disorders in Traditional Gamelan Craft Workers in Bali - Juli Suarbawa I Ketut Gde; Muhammad Yusuf; I Made Suarta; I Gede Oka Pujihadi (Unit Publikasi Ilmiah, P3M, Politeknik Negeri Bali, 2025)
This study investigates the effect of work posture and workplace environmental conditions on musculoskeletal disorders (MSDs) and fatigue among traditional gamelan craftsmen in Bali, Indonesia. Using a pre-experimental one-group pretest–posttest design, fifty-one male workers were assessed using the Nordic Body Map (NBM), the EORTC QLQ-C30 fatigue scale, and the Rapid Upper Limb Assessment (RULA). The results showed a significant increase in MSD scores from 29.72 to 48.90 and fatigue scores from 31.06 to 44.26 after a single four-hour work session (p < 0.001). RULA analysis indicated that 100% of workers performed tasks in moderate- to high-risk postures, with 36.8% requiring immediate ergonomic intervention. The most affected anatomical regions included the lower back, upper back, neck, and thighs. These findings suggest that prolonged static postures, floor-level working positions, and suboptimal workplace environmental conditions substantially contribute to physical strain. The results highlight the urgent need for ergonomic interventions tailored to traditional craft industries to reduce cumulative trauma risks and improve worker well-being.